PENDIDIKAN BERBASIS SASTRA LISAN (LUKISAN ANALITIK ATAS NILAI PEDAGOGI DALAM FOLKLOR ORANG WAKATOBI) (Education Based on Oral Literature (An Analytical Description of Pedagogical Values in Wakatobi People Folklore)) - Muhammad Alifuddin; Sumiman Udu; Laode Anhusadar (Kantor Bahasa Provinsi Sulawesi Tenggara, 2022)
This research is an analytic painting about the content of educational values in the oral literature of the people of Wakatobi. All data in this study were sourced from in-depth interviews, observations, and document studies. Considering this research is related to aspects of oral literature in the socio-cultural space, the data analysis was carried out using a hermeneutic phenomenology approach. Folklore in the form of folklore (tula-tula) and kabanti (folksong) are two forms of oral literature that are still used as educational media by Wakatobi people. This study found that the contents of the tula-tula and kabanti that grew in the cultural space of the Wakatobi people functioned as treasures of knowledge and entertainment value and contained ethical values. Through oral literature, the Wakatobi people consciously try to build values in order to maintain harmony with nature, microcosmic relations between humans, and macrocosm relations to the Creator. The characteristics of the learning model in the tula and kabanti, are more information-giving, in the form of facts and memories, generally one-way, and the style of the speaker/teacher is preferred in conveying messages, intonation, improvisation, enthusiasm, and systematic message. Penelitian ini merupakan lukisan analitik tentang muatan nilai pendidikan dalam sastra lisan orang Wakatobi. Seluruh data dalam penelitian ini bersumber dari hasil wawancara mendalam, pengamatan, serta studi dokumen. Mengingat penelitian ini terkait dengan aspek sastra lisan dalam ruang sosial budaya, analisis data dilakukan dengan menggunakan pendekatan fenomenologi hermeneutik. Folklor dalam bentuk cerita rakyat (tula-tula) dan kabanti (folksong) adalah dua bentuk sastra lisan yang hingga kini masih digunakan sebagai media pendidikan oleh orang Wakatobi. Penelitian ini menemukan bahwa muatan tula-tula dan kabanti yang tumbuh dalam ruang budaya orang Wakatobi tidak hanya berfungsi sebagai khazanah pengetahuan dan bernilai hiburan, tetapi juga mengandung nilai-nilai etika. Melalui sastra lisan, orang Wakatobi secara sadar berusaha membangun nilai dalam rangka menjaga harmoni dengan alam, hubungan mikrokosmis sesama manusia, dan hubungan makrokosmos kepada sang Pencipta. Karakteristik model pembelajaran dalam tula-tula dan kabanti lebih bersifat pemberian informasi berupa fakta dan ingatan, umumnya bersifat satu arah, dan gaya penutur/guru lebih diutamakan dalam menyampaikan pesan, intonasi, improvisasi, semangat, dan sistematika pesan.